Aceclofenac: therapeutic effectiveness in osteoarthrosis - Tatyana Alekseyevna Raskina (Современная ревматология)
The place of aceclofenac in a group of nonsteroidal anti-inflammatory drugs and its efficacy in osteoarthrosis are discussed.